2015
DOI: 10.1038/srep08922
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic variants in differentiated thyroid cancer and assessment of the cumulative risk

Abstract: A genome-wide association study (GWAS) performed on a high-incidence Italian population followed by replications on low-incidence cohorts suggested a strong association of differentiated thyroid cancer (DTC) with single nucleotide polymorphisms (SNPs) at 9q22.33, 2q35, 20q11.22-q12 and 14q24.3. Moreover, six additional susceptibility loci were associated with the disease only among Italians. The present study had two aims, first to identify loci involved in DTC risk and then to assess the cumulative effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 37 publications
(38 reference statements)
3
31
0
Order By: Relevance
“…However-since MMR proteins functionally interact within the same pathwayan additive (or even multiplicative) effect with other MMR SNPs is possible. Supporting this hypothesis, several studies have shown that, although individual susceptibility alleles may have only a modest effect, DTC risk may be substantially increased when multiple risk variants are considered together (15,16). Considering the strong genetic component of DTC susceptibility, such a role for gene-gene interactions is likely (16).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However-since MMR proteins functionally interact within the same pathwayan additive (or even multiplicative) effect with other MMR SNPs is possible. Supporting this hypothesis, several studies have shown that, although individual susceptibility alleles may have only a modest effect, DTC risk may be substantially increased when multiple risk variants are considered together (15,16). Considering the strong genetic component of DTC susceptibility, such a role for gene-gene interactions is likely (16).…”
Section: Discussionmentioning
confidence: 88%
“…Recently performed GWAS (6-12) have provided valuable contribution but, even so, explain only part of the estimated heritability of DTC (11,15,16). Several reasons may contribute: it is possible that the highly stringent criteria applied to GWAS to prevent false-positive findings result in the exclusion of SNPs truly associated with DTC risk (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This limitation is solved by genome-wide association studies (GWASs) in which the whole genome is analyzed without formulating any a priori hypothesis. GWASs on DTC allowed discovering novel variants, including those near FOXE1, DIRC3, NKX2-1 (15)(16)(17) and, more recently, those near IMMP2L, RARRES1, SNAPC4/CARD9, ARSB, BATF, DHX35, SPATA13, GALNTL4, and FOXA2 (18)(19)(20). However, to ensure a high quality and to prevent false-positive findings, highly stringent criteria are applied in the GWASs with the disadvantage of excluding SNPs truly associated with the risk.…”
Section: Introductionmentioning
confidence: 99%